A study on the functionality effects of the potassium salt concentration in skinless longanisa - Avila, Karen A..; Francisco, Ma. Leonora dL. (1999., 1999)
Total and partial replacement of NaCl with KCl at 0%, 25%, 50%, 75% and 100% levels were used to determine the effects of KCl salt concentrations on the sensory characteristics, cooking loss, water-holding capacity, pH and purge losses on skinless pork longanisa. No significant differences (α = 0.05) were found in the texture, moistness, color, cooking loss and water-holding capacity of the samples in all treatments. No purge losses were observed in all the samples after a storage period of 14 days at 4°C. Significant difference (α = 0.05) were found in the overall acceptability, saltiness, off-flavor, flavor acceptability and pH of the samples in all treatment levels. Data suggests that increasing the KCl concentration decreases the overall acceptability of the product but it is possible to substitute up to 50% of the NaCl in skinless pork longanisa without detrimental effects on the palatability of the product.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Sausages; Meat -- Processing; Ptassium salts